Phytochemical screening, antibacterial and antioxidant assessment of Leuconotis eugenifolia leaf extract : - - Praptiwi Praptiwi; DEWI WULANSARI; AHMAD FATHONI; NOTO HARNOTO; ROSSI NOVITA; ALFRIDSYAH; ANDRIA AGUSTA (Nusantara Bioscience, 2020)
Abstract. Praptiwi, Wulansari D, Fathoni A, Harnoto N, Novita R, Alfridsyah, Agusta A. 2020. Phytochemical screening, antibacterial and antioxidant assessment of Leuconotis eugenifolia leaf extract. Nusantara Bioscience 12: 79-85. Traditionally, sitahe (Leuconotis eugenifolia (Wall. Ex G. Don) A.DC) has been used to maintain stamina by Aceh peoples, Indonesia. The use of L. eugenifolia mainly as a spice on a traditional cuisine “ie bu peudah”. This research was conducted to determine the phytoconstituents of L. eugenifolia leaf extracts, and to investigate their antioxidant potential using 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging and antibacterial activity against Staphylococcus aureus and Escherichia coli. Phytochemical screening was carried out using standard methods. L. eugenifolia leaves were extracted successively with n-hexane, dichloromethane, ethyl acetate, methanol, and water. Obtained extracts were tested qualitatively for antioxidant and antibacterial by the TLC-bioautography method, followed by quantitative analysis to determine the MIC and IC50 value using the microdilution method on 96-well microplate. The results showed that it contained alkaloids, flavonoids, steroids, triterpenoids, saponins, phenolics, and tannins. The highest levels of phenolic (259.0486 ± 0.1203 mg GAE/g extract) and flavonoids (84.6575 ± 0.0237 mg QE/g extract) were found in ethyl acetate extract, and dichloromethane, respectively. The antibacterial activity of n-hexane and dichloromethane extracts is moderate against E. coli, and weak against S. aureus. Ethyl acetate extract, methanol, and water extracts have very strong antioxidant activity. L. eugenifolia leaf extracts may be promising new antioxidant sources.